2017
DOI: 10.1038/bjc.2017.330
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 study of ARQ 087, an oral pan-FGFR inhibitor in patients with advanced solid tumours

Abstract: Background:ARQ 087 is an orally administered pan-FGFR inhibitor with multi-kinase activity. This Phase 1 study evaluated safety, pharmacokinetics, and pharmacodynamics of ARQ 087 and defined the recommended Phase 2 dose (RP2D).Methods:Patients with advanced solid tumours received ARQ 087 administered initially at 25 mg every other day and dose-escalated from 25 to 425 mg daily (QD) continuous dosing. FGF19, 21, 23, and serum phosphate were assessed as potential biomarkers of target engagement.Results:80 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 16 publications
(33 reference statements)
4
52
0
Order By: Relevance
“…BGJ398, another selective FGFR1‐3 inhibitor, showed antitumor activity in several tumor types and had a tolerable safety profile in a phase I study in patients with advanced solid tumors, whereas JNJ‐42756493, a pan‐FGFR inhibitor recently approved by the FDA for urothelial carcinoma, showed a clinical response with acceptable safety in a similar patient population . Similar findings have been reported for the pan‐FGFR inhibitors LY2874455 and ARQ 087 . Clinical trials are ongoing for other highly selective FGFR inhibitors in development, such as TAS‐120 and INCB054828, in which patients are screened for FGFR abnormalities using next‐generation sequencing or FISH techniques.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…BGJ398, another selective FGFR1‐3 inhibitor, showed antitumor activity in several tumor types and had a tolerable safety profile in a phase I study in patients with advanced solid tumors, whereas JNJ‐42756493, a pan‐FGFR inhibitor recently approved by the FDA for urothelial carcinoma, showed a clinical response with acceptable safety in a similar patient population . Similar findings have been reported for the pan‐FGFR inhibitors LY2874455 and ARQ 087 . Clinical trials are ongoing for other highly selective FGFR inhibitors in development, such as TAS‐120 and INCB054828, in which patients are screened for FGFR abnormalities using next‐generation sequencing or FISH techniques.…”
Section: Introductionsupporting
confidence: 56%
“…Reasons for TEAE‐related dose interruptions included nausea (n = 3), vomiting (n = 2), anorexia (n = 2), nasopharyngitis (n = 1), and decreased neutrophil count (n = 1). Selective FGFR inhibition has been associated with an increased risk of hyperphosphatemia and eye toxicity, including retinal detachment . In the present study, there were nine AE of hyperphosphatemia and three AE of retinal detachment, but all were <grade 3 in severity and did not lead to dose reduction or discontinuation.…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…Preclinical and phase I studies have suggested that these compounds have potent and selective anti-tumor activity against FGFRmutated cancers (80)(81)(82)(83). A recently developed monoclonal antibody against FGFR2 (BAY1179470) showed tumor suppressive potential in tumors with high FGFR2 expression (84).…”
Section: Fgfr2 Fusionsmentioning
confidence: 99%
“…A recent study showed FGF19 and 21 could act as biomarkers during treatment follow‐up using pan‐FGFR inhibitors in patients with advanced solid tumor. FGF19 and 21 were found to be increased during each treatment with a dose‐dependent trend, which implies that it reflects the patients' therapeutic response .…”
Section: Discussionmentioning
confidence: 85%